Angry Responses to Infant Challenges: Parent, Marital, and Child Genetic Factors Associated With Harsh Parenting. Issue 1 (2nd February 2015) - Hajal, Nastassia; Neiderhiser, Jenae; Moore, Ginger; Leve, Leslie; Shaw, Daniel; Harold, Gordon; Scaramella, Laura; Ganiban, Jody; Reiss, David
<x xml:space="preserve">Abstract</x> This study examined genetic and environmental influences on harsh parenting of adopted 9‐month‐olds (N = 503), with an emphasis on positive child‐, parent‐, and family‐level characteristics. Evocative gene–environment correlation (rGE) was examined by testing the effect of both positive and negative indices of birth parent temperament on adoptive parents' harsh parenting. Adoptive fathers' harsh parenting was inversely related to birth mother positive temperament, indicating evocative rGE, as well as to marital quality. Adoptive parents' negative temperamental characteristics were related to hostile parenting for both fathers and mothers. Findings support the importance of enhancing positive family characteristics in addition to mitigating negative characteristics, as well as engaging multiple levels of the family system to prevent harsh parenting.